Ten years of chest MRI for patients with cystic fibrosis: translation from the bench to clinical routine = 10 Jahre Thorax-MRT für Patienten mit zystischer Fibrose : Übertragung vom Versuchsstadium in dieklinische Routine - Leutz-Schmidt, Patricia; Eichinger, Monika; Stahl, Mirjam; Sommerburg, Olaf; Biederer, Jürgen; Kauczor, Hans-Ulrich; Puderbach, Michael; Mall, Marcus A.; Wielpütz, Mark Oliver (Der Radiologe, 2019)
Despite recent advances in our knowledge about the pathophysiology and treatment of cystic fibrosis (CF), pulmonary involvement remains the most important determinant of morbidity and mortality in patients with CF. Since lung function testing may not be sensitive enough for subclinical disease progression, and because young children may have normal spirometry results over a longer period of time, imaging today plays an increasingly important role in clinical routine and research for the monitoring of CF lung disease. In this regard, chest magnetic resonance imaging (MRI) could serve as a radiation-free modality for structural and functional lung imaging.
Gesehen am 31.03.2020